Market-based approaches to the understanding of quality management in higher education (Journal of Economic Research & Business Administration, 2015)
This article describes the relationship of the concept of quality and satisfaction. In considering and detail the concept of quality from different angles and visions of scientists, we have define the direction of future aspects. Further, the content of the stages of development are considered quality management as a process of evolution, which revealed the need for understanding the importance of a constant search for relevant solutions in the field of quality management. Quality in education is considered, on the basis of existing visions and results of labor, where the emphasis is on the search and examination due to satisfaction. Control the quality of education requires a distinction between the spheres of education, or stages of education. In the last paragraph, we have considered the importance of the market to meet the manpower needs. The paper deals with the employment of graduates, as well as the definition of the links between businesses and schools.
Keywords: Quality; quality management; quality of higher education; quality management education; human resources; quality management processes